1997
DOI: 10.1148/radiology.204.3.9280242
|View full text |Cite
|
Sign up to set email alerts
|

Interventional breast MR imaging: clinical use of a stereotactic localization and biopsy device.

Abstract: MR imaging-guided stereotactic hook-wire placement and excisional biopsy are accurate and effective in managing lesions identified at only breast MR imaging. MR imaging-guided core biopsy holds promise for allowing a definite work-up of these lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
0
9

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(117 citation statements)
references
References 0 publications
5
103
0
9
Order By: Relevance
“…If BI-RADS ® 4 or 5 findings detected on diagnostic MRI are no longer visible, it is necessary to first rule out technical causes. For example, strong breast compression may result in reduced contrast enhancement [25,27,30,31]. If there is reasonable suspicion that this is the case, a new MRI with reduced breast compression would be recommended.…”
Section: Mri-guided Lesion Markingmentioning
confidence: 99%
See 1 more Smart Citation
“…If BI-RADS ® 4 or 5 findings detected on diagnostic MRI are no longer visible, it is necessary to first rule out technical causes. For example, strong breast compression may result in reduced contrast enhancement [25,27,30,31]. If there is reasonable suspicion that this is the case, a new MRI with reduced breast compression would be recommended.…”
Section: Mri-guided Lesion Markingmentioning
confidence: 99%
“…In these studies, MRI-guided lesion marking proved to be a valid and precise method [36]. Larger studies involving n> 50 lesions have reported technical success rates of 97 -98 % [30,37,38]. However, MRI-guided lesion marking has since been replaced by MRI-VAB and is only warranted in isolated cases (see above).…”
mentioning
confidence: 99%
“…The freehand method of MRI-guided breast interventions (8-10) differs from other facilities that use a grid and contrast enhancement prior to needle placement (6,7,(13)(14)(15)(16)(17)(18). This method uses noncontrast T1-weighted scans to identify unenhanced targets in the noncompressed breast without a grid (8,9).…”
Section: Vacnbmentioning
confidence: 99%
“…Although MR-guided biopsy was not possible in current study, we included it in Fig. 3 because it has been reported to be the effective method in determining the nature of breast lesion that is undetectable in the other modalities (11,23).…”
Section: Discussionmentioning
confidence: 99%